2016
DOI: 10.1002/2015jb012179
|View full text |Cite
|
Sign up to set email alerts
|

Micropolar effect on the cataclastic flow and brittle‐ductile transition in high‐porosity rocks

Abstract: A micromechanical distinct element method (DEM) model is adopted to analyze the grain‐scale mechanism that leads to the brittle‐ductile transition in cohesive‐frictional materials. The cohesive‐frictional materials are idealized as particulate assemblies of circular disks. While the frictional sliding of disks is sensitive to the normal compressive stress exerted on contacts, normal force can be both caused by interpenetration and long‐range cohesive bonding between two particles. Our numerical simulations ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…Hence, we conclude that the slope (the hardening behavior) of σ d -ε a curves is governed by slip along shear bands. Our findings support results from constitutive and discrete element models of granular deformation focusing on intergranular sliding without considering intragranular cracking (e.g., Tengattini et al, 2014;Zheng et al, 2016). These models reproduce the essential features of the stress-strain and compaction behavior associated with the transition to cataclastic flow observed in laboratory.…”
Section: Role Of Mesoscale Shear Bands On Granular Deformationsupporting
confidence: 85%
See 2 more Smart Citations
“…Hence, we conclude that the slope (the hardening behavior) of σ d -ε a curves is governed by slip along shear bands. Our findings support results from constitutive and discrete element models of granular deformation focusing on intergranular sliding without considering intragranular cracking (e.g., Tengattini et al, 2014;Zheng et al, 2016). These models reproduce the essential features of the stress-strain and compaction behavior associated with the transition to cataclastic flow observed in laboratory.…”
Section: Role Of Mesoscale Shear Bands On Granular Deformationsupporting
confidence: 85%
“…The observation that many shear bands in the semibrittle faulting regime show relatively large offsets (with offset to length ratio of up to~3%; Table 2) suggests that the bands are long-lived. This inference agrees with permanent, mesoscale bands predicted from models where grain contacts lose shear strength once slip occurs (Wang et al, 2008;Zheng et al, 2016), but differs from short-lived bands shown in models where the once-slipped contacts regain the strength (Aharonov & Sparks, 2002).…”
Section: Role Of Mesoscale Shear Bands On Granular Deformationsupporting
confidence: 81%
See 1 more Smart Citation
“…Nonlocal models (Guy et al., 2018; Tvergaard & Needleman, 1995), micropolar continua (Suh et al., 2020; Zheng et al., 2016), gradient‐damage models (de Borst & Verhoosel, 2016; Nguyen et al., 2018), enhanced‐strain methods (Armero & Garikipati, 1996), viscoplastic regularization (Duretz et al., 2020; Simo & Ju, 1987), or other extended formulations are proven methods to mitigate the mesh‐dependent effects (Parisio et al., 2019; Yoshioka et al., 2019). In this work, we apply a mesh‐adjusted softening parameter α d and all simulations are performed with the same discretization (quadrilateral elements of 0.5 mm size).…”
Section: Localized Deformationmentioning
confidence: 99%